Undertaking the biological sex assessment of human remains: The applicability of minimally-invasive methods for proteomic sex estimation from enamel peptides - Brůžek, Jaroslav; Mikšík, Ivan; Pilmann Kotěrová, Anežka; Morvan, Marine; Drtikolová Kaupová, Sylva; Santos, Fréderic; Danielisová, Alžběta; Zazvonilová, Eliška; Maureille, Bruno; Velemínský, Petr (My University, 2024)
Being a part of the cultural heritage, skeletal human remains and grave objects are often the only evidence of people who lived many years, or even centuries or millennia, ago, and their preservation for future generations is thus of the utmost importance. The first task in analyzing skeletal remains is to build a biological profile of the individual, including in particular a sex estimation. Recently developed proteomic sex analysis, based on the detection of two sex-dependent forms of the amelogenin protein in tooth enamel, could offer a minimally-invasive and reliable approach applicable to both recent and past populations. The aims of the present study are: 1) to validate the proteomic sex estimation approach with a delicate, minimally-destructive protocol using protein etching in recent and sub-recent identified samples of adult individuals; 2) for the first time, to evaluate the invasiveness of the extraction of amelogenin protein from teeth for proteomic analysis via scanning electron microscope (SEM) and microcomputed tomography (micro-CT); 3) to apply the method to an archaeological sample of unknown adult and juvenile individuals. An assemblage of 60 teeth (32 males and 28 females) of recent and sub-recent origin was used to validate the approach. A sub-sample of 20 teeth (10 males and 10 females) was used to assess the invasiveness of the amelogenin extraction procedure. For the application of the method, samples of 15 adult and 32 juvenile teeth, both originating from medieval populations, were used. Proteomic sex estimation achieved 100% accuracy in this sample. An SEM and micro-CT comparison of the dental surfaces before and after chemical treatment showed an approximately 10% loss of enamel and only 2% loss of dentine. The suitability and minimally-invasive character of the protocol for proteomic analysis in biological sex estimation was demonstrated, as was its applicability to archaeological samples.
Provádění biologického posouzení pohlaví lidských ostatků: Použitelnost minimálně invazivních metod pro proteomický odhad pohlaví ze sklovinných peptidů
Keywords: Human skeletal collections; Cultural heritage; Proteomics; Sex estimation; Sampling